1999
DOI: 10.1042/bj3390541
|View full text |Cite
|
Sign up to set email alerts
|

Light-dependent changes in redox status of the plastidic acetyl-CoA carboxylase and its regulatory component

Abstract: Plastidic acetyl-CoA carboxylase (ACCase; EC 6.4.1.2), which catalyses the synthesis of malonyl-CoA and is the regulatory enzyme of fatty acid synthesis, is activated by light, presumably under redox regulation. To obtain evidence of redox regulation in vivo, the activity of ACCase was examined in pea chloroplasts isolated from plants kept in darkness (dark-ACCase) or after exposure to light for 1 h (light-ACCase) in the presence or absence of a thiol-reducing agent, dithiothreitol (DTT). The protein level was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 12 publications
(16 reference statements)
5
17
0
Order By: Relevance
“…Whereas FA synthesis is known to be light regulated at the level of ACCase by the redox mechanism (Kozaki and Sasaki, 1999), here we observe that genes involved in FA synthesis are also coordinately regulated at the transcriptional level. This involves the dark-induced downregulation of almost all key pathway enzymes, including elements of the FA synthase complex: KASI, KASIII, hydroxyl-ACP dehydrase, and enoyl-ACP reductase ENR1; the biotin carboxylase subunit of ACCase, malonyl-CoA:ACT malonyltransferase, the longchain acyl-CoA synthetase LACS9, the acyl-ACP synthetase AAE15; and components of the pyruvate dehydrogenase complex: one of the genes for b-PDH (At1g30120) and LPD2 ( Figure 4B).…”
Section: Fa Synthesissupporting
confidence: 57%
“…Whereas FA synthesis is known to be light regulated at the level of ACCase by the redox mechanism (Kozaki and Sasaki, 1999), here we observe that genes involved in FA synthesis are also coordinately regulated at the transcriptional level. This involves the dark-induced downregulation of almost all key pathway enzymes, including elements of the FA synthase complex: KASI, KASIII, hydroxyl-ACP dehydrase, and enoyl-ACP reductase ENR1; the biotin carboxylase subunit of ACCase, malonyl-CoA:ACT malonyltransferase, the longchain acyl-CoA synthetase LACS9, the acyl-ACP synthetase AAE15; and components of the pyruvate dehydrogenase complex: one of the genes for b-PDH (At1g30120) and LPD2 ( Figure 4B).…”
Section: Fa Synthesissupporting
confidence: 57%
“…The regulatory properties of ACCase are increasingly evident (Post-Beittenmiller et al, 1992;Hunter and Ohlrogge, 1998;Kozaki and Sasaki, 1999;Savage and Ohlrogge, 1999), and the role of this enzyme in determining oil content has been demonstrated by increasing the plastidial ACCase activity in embryos of transgenic rapeseed to gain an increase in oil content under certain growth conditions (Roesler et al, 1997). Recently, Bao and Ohlrogge (1999) have shown that the rate of oil synthesis by embryos of oilseed species can be stimulated in vitro by the supply of free fatty acids, providing evidence that the supply of de novo-synthesized fatty acyl groups to the lipid biosynthetic pathway can be a limiting step.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of the reducing agent dithiothreitol to ACCase showed that CT, but not BC, is activated. 64) Pea recombinant CT expressed in E. coli has properties similar to those of authentic CT and is redox-regulated. 21) Site-directed mutagenesis showed that one cysteine residue in the -CT and one cysteine in the -CT involved in redox regulation form an intermolecular disulfide bond between and subunits.…”
Section: Regulation By Redoxmentioning
confidence: 99%